INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN MEMBACA - R. Saleh, Yuwin (Irfani, 2015)
Weak national character demand the integration of the character education in each subject, also in reading, it can be done through the selection of materials, the use of learning and authentic assessment.